A sweet taste receptor‐dependent mechanism of glucosensing in hypothalamic tanycytes. Issue 5 (16th February 2017) - Benford, Heather; Bolborea, Matei; Pollatzek, Eric; Lossow, Kristina; Hermans‐Borgmeyer, Irm; Liu, Beihui; Meyerhof, Wolfgang; Kasparov, Sergey; Dale, Nicholas
Abstract: Hypothalamic tanycytes are glial‐like glucosensitive cells that contact the cerebrospinal fluid of the third ventricle, and send processes into the hypothalamic nuclei that control food intake and body weight. The mechanism of tanycyte glucosensing remains undetermined. While tanycytes express the components associated with the glucosensing of the pancreatic β cell, they respond to nonmetabolisable glucose analogues via an ATP receptor‐dependent mechanism. Here, we show that tanycytes in rodents respond to non‐nutritive sweeteners known to be ligands of the sweet taste (Tas1r2/Tas1r3) receptor. The initial sweet tastant‐evoked response, which requires the presence of extracellular Ca 2+, leads to release of ATP and a larger propagating Ca 2+ response mediated by P2Y1 receptors. In Tas1r2 null mice the proportion of glucose nonresponsive tanycytes was greatly increased in these mice, but a subset of tanycytes retained an undiminished sensitivity to glucose. Our data demonstrate that the sweet taste receptor mediates glucosensing in about 60% of glucosensitive tanycytes while the remaining 40% of glucosensitive tanycytes use some other, as yet unknown mechanism. Main Points: Tanycytes respond to non‐nutritive sweet‐tasting compounds. Deletion of the Tas1r2 gene, an essential component of the sweet taste receptor, shows that around 60% of glucosensitive tanycytes sense glucose via the sweet taste receptor.